World Bank Outlook 2050 Strategic Directions Note : Supporting Countries to Meet Long-Term Goals of Decarbonization - Mukhi, Neha (World Bank, Washington, DC, 2020)
Outlook 2050 examines how the World Bank can help countries plan for and achieve long-term decarbonization: through country programs, technical assistance, lending, and knowledge products. It identifies key trends in technology, markets, financing instruments, and consumer priorities, and examines their implications for climate action, economic growth strategies and development. Supporting countries in a transition to long-term decarbonization requires the World Bank to not only look 3–5 years ahead, roughly equivalent to typical election cycles, but look decades ahead, and then work with our clients to determine the near- and mid-term implications. It will also mean supporting the implementation of economy-wide strategies as well as cross-sectoral initiatives, not only focusing on single-sector initiatives, such as individual energy or transportation projects. Coinciding with a need for a major, global economic recovery – triggered by the COVID-19 (coronavirus) pandemic – this ‘whole of economy' approach to deliver better growth and a better climate could provide the sustainable and resilient foundation for countries as they build – or rebuild – their economies. The Outlook 2050 approach prioritizes four economy-wide strategic directions: 1. Embed long-term climate priorities in country macroeconomic frameworks, to ensure that those frameworks, which guide fiscal policy and major national investments, properly account for climate risks and the benefits of ambitious climate action. 2. Embed long-term climate planning in national budgets and expenditure frameworks, to provide adequate budgetary support for climate action, optimize the overall allocation of public resources, and unlock private financial flows. 3. Embed long-term climate objectives in financial sector regulations and incentives, to ensure that the sector is resilient both to climate change impacts and to low-carbon transition risks, and to mobilize finance for climate action. 4. Embed long-term climate objectives in systems planning, to integrate climate with economic, social inclusion, and other objectives; assess cross-sectoral links and regional impacts; and identify trade-offs and synergies.